1989
DOI: 10.1073/pnas.86.10.3539
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease H activities associated with viral reverse transcriptases are endonucleases.

Abstract: A series of test substrates have been synthesized to establish the effect of termini on the putative exoribonuclease H activity of reverse transcriptase. Recombinant reverse transcriptase from human immunodeficiency virus, natural enzyme from avian myeloblastosis virus, and a known endonuclease, Escherichia coli ribonuclease H, cleaved relaxed, circular, covalently closed plasmids in which 770 consecutive residues of one strand were ribonucleotides. The avian enzyme also deadenylated capped globin mRNA with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 32 publications
(11 reference statements)
4
20
0
Order By: Relevance
“…The RNase H activity of reverse transcriptase acts as an endonuclease that hydrolyzes the RNA strand in an RNA/DNA hybrid to generate 5′ phosphate and 3′ hydroxyl ends (Krug and Berger, 1989;DeStefano et al, 1991a;Champoux, 1993). The isolated MoMLV RNase H domain retains enzymatic activity (Tanese and Goff, 1988), but is unable to carry out specific cleavages such as removal of the tRNA or PPT primers in vitro (Schultz and Champoux, 1996;Zhan and Crouch, 1997).…”
Section: Enzyme Activitymentioning
confidence: 99%
“…The RNase H activity of reverse transcriptase acts as an endonuclease that hydrolyzes the RNA strand in an RNA/DNA hybrid to generate 5′ phosphate and 3′ hydroxyl ends (Krug and Berger, 1989;DeStefano et al, 1991a;Champoux, 1993). The isolated MoMLV RNase H domain retains enzymatic activity (Tanese and Goff, 1988), but is unable to carry out specific cleavages such as removal of the tRNA or PPT primers in vitro (Schultz and Champoux, 1996;Zhan and Crouch, 1997).…”
Section: Enzyme Activitymentioning
confidence: 99%
“…Results from a fragment ligation assay have suggested that the 11-nt RNA cleavage product generated in vivo has a 3Ј-OH terminus (18). Since the RT-associated RNase H activity performs primarily as an endonuclease, which cleaves the phosphodiester bonds in the RNA strand, yielding 3Ј-OH and 5Ј-PO 4 termini (15,27), the Tf1 RT-directed production of the RNA selfprimer is also likely to generate such ends. Given that retroviral RTs (as opposed to RTs of some bacterial retroelements) specifically prime in vitro DNA synthesis from the 3Ј-OH group of the RNA primer (13,27,28), the finding presented in this study that the Tf1 RT-generated primer is functional in DNA synthesis implies that this in vitro-produced primer also has a 3Ј-OH terminus.…”
mentioning
confidence: 99%
“…Despite the similarities in the active-site conformations and the modes of action between reverse-transcriptase RNase H [23,241 and E. coli RNase HI [l], different catalytic niechanisms have been proposed for these enzymes. Identification of a single Mg2'-binding site in the E. coli enzyme [2S, 261 allows us to propose a carboxylate-hydroxyl relay mechanism for this enzyme 1271.…”
mentioning
confidence: 99%